Current trends in the development of Russian higher education in the context of the global economy digitalization - E. S. Novikova (Вестник университета)
The analysis of current changes in the field of distance education, and, in particular, higher education among domestic and western universities is presented. The additional impact of the COVID-19 pandemic on the sharp increase in the popularity and use of online education in various segments of the educational process, starting from preschool and ending with corporate programs of companies is noted. The key advantages and disadvantages of online education are identified, as well as emerging risks for Russian Universities and the domestic economy when introducing distance learning.